2020
DOI: 10.1021/acsami.0c14248
|View full text |Cite
|
Sign up to set email alerts
|

Large Field Enhancement of Nanocoral Structures on Porous Si Synthesized from Rice Husks

Abstract: Silicon (Si) is a highly abundant, environmentally benign, and durable material and is the most popular semiconductor material; and it is used for the field enhancement of dielectric materials. Porous Si (PSi) exhibits high functionality due to its specific structure. However, the field enhancement of PSi has not been clarified sufficiently. Herein, we present the field enhancement of PSi by the fluorescence intensity enhancement of a dye molecule. The raw material used for producing PSi was rice husk, a bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…Si microstructures with roughness exhibit higher EFs. 36 Time and Cost of Preparing the 2D-SiWA Enhancement Substrate. We evaluated the production time and cost of fabricating a 2D-SiWA as a sensing substrate.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Si microstructures with roughness exhibit higher EFs. 36 Time and Cost of Preparing the 2D-SiWA Enhancement Substrate. We evaluated the production time and cost of fabricating a 2D-SiWA as a sensing substrate.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…For this reason, many researchers have experimentally and theoretically investigated the field enhancement of submicron-structured Si materials for various shapes, including spheres, 30,31 dimers, 32 disks, 33 doughnuts, 34 pillars, 35 and coral structures. 36 Research has demonstrated a large field enhancement in the visible to near IR regions, whereby the performances of solar cells, 37−45 biomedical sensors, 46−49 optical tweezers, 50 and high-color light sources 51 are improved in a wide spectral region.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The reduction reaction of SiO 2 was conducted using magnesiothermic reduction. Namely, SiO 2 powders (300 mg) were mixed with Mg (350 mg) and NaCl (846 mg) powders in an Ar atmosphere, and Mg and NaCl were used as a reduction reagent and a heat bath, respectively. The mixed powders were placed in a reaction vessel purged with Ar gas and were heated at 650 °C for 2 h using a tube furnace.…”
Section: Experimental Proceduresmentioning
confidence: 99%